2007
DOI: 10.1097/aco.0b013e3280c60c3b
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco dependence in surgical patients

Abstract: The fact that the perioperative period represents an excellent opportunity to help surgical patients quit smoking is becoming increasingly apparent. Although these efforts, and the evidence base to support them, are still at an early stage of development, seizing this opportunity will benefit both the short and long-term health of our patients who smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
2
26
0
3
Order By: Relevance
“…Covariates included age, race and marital status from SHEP, disability due to military service from NPCD, and time from AUDIT-C to surgery. Cigarette smoking status in the past year, 36 the American Society of Anesthesiologists classification (ASA class) documented by anesthesiologists, and the surgical facility were obtained from VASQIP. Additional covariates were selected from 45 pre-operative measures collected by VASQIP that have demonstrated superiority over other measures for surgical riskadjustment.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates included age, race and marital status from SHEP, disability due to military service from NPCD, and time from AUDIT-C to surgery. Cigarette smoking status in the past year, 36 the American Society of Anesthesiologists classification (ASA class) documented by anesthesiologists, and the surgical facility were obtained from VASQIP. Additional covariates were selected from 45 pre-operative measures collected by VASQIP that have demonstrated superiority over other measures for surgical riskadjustment.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking is associated with increased postoperative morbidity and mortality. [1][2][3] This is a major concern as up to 20% of surgical patients are smokers. 4,5 A recent large observational study of non-cardiac surgical patients reported that smoking is associated with a 38% increase in the risk of perioperative death and a 30-109% increase in the risk of serious postoperative complications, depending on the type of complication.…”
Section: Résumémentioning
confidence: 99%
“…Group for number of cigarettes smoked/day TLIF TS Fig. 2 Dose-response relationship between group for number of cigarettes smoked and the reduction in pain intensity (worst of leg pain or back pain)) from preoperatively to 24 months FU (note, there are a number of overlapping points and hence the number of points shown does not equal the total number of data points contributing to the analysis) In addition to the higher perioperative risks [27], higher wound-related complications, and higher rate of non-union associated with smoking, even poorer results in terms of patient-rated outcome should be expected if TS is chosen as the fusion technique in smokers.…”
Section: Discussionmentioning
confidence: 99%